Elucidating Cannabidiol Binding Sites On The α7 Nicotinic Acetylcholine Receptor - Chrestia, Juan Facundo (2024)
The α7 nicotinic receptor is an ACh-gated channel present in the nervous system and in non-neuronal cells. Reduced activity of α7 has been linked to neurological and neurodegenerative disorders, while increased activity could contribute to cancer progression. α7 is a target of cannabidiol (CBD), which is of great interest due to its widespread use, therapeutic properties, and lack of psychoactive effects. By patch clamp recordings, we showed that CBD mediates two distinct actions on α7 function occurring at different time scales. CBD rapidly inhibits the frequency of activation episodes, while after several minutes, it causes an additional delayed effect evidenced by the appearance of prolonged activation episodes. To predict the binding sites of CBD, we performed molecular dynamics simulations of α7 and CBD in coarse-grained representation. α7 resting and desensitized states were embedded in a POPC:POPA:CHOL membrane and simulated in the presence ofCBDmolecules. Several potential binding sites were identified for both receptor states. Representative structures were backmapped to atomistic representation and each one was simulated to gain deeper insight into the stability and interactions. In both states, themost stable binding site was located in the top portion of the extracellular domain. Contact analysis was performed and several residues were selected for mutagenesis studies. Compared to the wild-type receptor, electrophysiological recordings with mutants showed different responses to CBD, ranging from reduced sensitivity for the rapid inhibitory effect to increased sensitivity for the kinetic changes. These results confirm the involvement of the candidate residues in the allosteric mechanism underlying CBD´s effect on α7 and suggest that different residues govern the different effects.